Increasing community environmental awareness, participation in conservation, and livelihood enhancement through tourism. Issue 5 (4th May 2022) - Ghaderi, Zahed; Shahabi, Elham; Fennell, David; Khoshkam, Mana
ABSTRACT: In line with social exchange theory, this case study explores how a previously indifferent and unsympathetic local community participates in the conservation of Touran National Park through community-based tourism. An in-depth analysis of local community members, local authorities, and NGOs revealed that due to changes in society's socio-cultural structure, the community's awareness of conservation has significantly increased and resulted in active participation in natural and cultural heritage. The findings provide an alternative to social exchange theory, suggesting that benefits should generally outweigh human social interaction and behaviour calculus costs. Furthermore, rural youth and women have become much more prominent despite many public participation dilemmas and rigid government structures. Finally, theoretical and practical implications for future research are discussed.